2012
DOI: 10.1097/jto.0b013e31823c4c1b
|View full text |Cite
|
Sign up to set email alerts
|

Detection of EGFR Mutation Status in Lung Adenocarcinoma Specimens with Different Proportions of Tumor Cells Using Two Methods of Differential Sensitivity

Abstract: Highly sensitive methods, such as PNA clamping, may be superior to direct sequencing for the detection of EGFR mutations in diagnostic specimens with a low proportion of tumor cells. Direct sequencing may be more representative when diagnostic specimens with a high proportion of tumor cells are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 26 publications
(42 reference statements)
2
65
1
1
Order By: Relevance
“…However, other studies using manual microdissection failed to show intra-tumoural heterogeneity of EGFR mutations [22][23][24]. In addition, studies comparing EGFR mutation status of biopsies and resection specimens revealed no discrepancies (table 2) [26][27][28]. This suggests that, in some NSCLCs heterogeneous for EGFR mutation [17,29,30], the number of tumour cells showing different mutational patterns in the primary tumour is very small and, thus, easily obscured by the predominant population and not detectable with usual methods.…”
Section: The Selection Of Biopsy Sitementioning
confidence: 86%
See 4 more Smart Citations
“…However, other studies using manual microdissection failed to show intra-tumoural heterogeneity of EGFR mutations [22][23][24]. In addition, studies comparing EGFR mutation status of biopsies and resection specimens revealed no discrepancies (table 2) [26][27][28]. This suggests that, in some NSCLCs heterogeneous for EGFR mutation [17,29,30], the number of tumour cells showing different mutational patterns in the primary tumour is very small and, thus, easily obscured by the predominant population and not detectable with usual methods.…”
Section: The Selection Of Biopsy Sitementioning
confidence: 86%
“…This suggests that, in some NSCLCs heterogeneous for EGFR mutation [17,29,30], the number of tumour cells showing different mutational patterns in the primary tumour is very small and, thus, easily obscured by the predominant population and not detectable with usual methods. However, this intra-tumoural heterogeneity of EGFR mutations might partially account for the discrepancies in clinical response to EGFR-TKIs in EGFR-mutated patients and for cases with unexplained primary and secondary resistance [28,31,32]. In the clinical setting, the overall EGFR status of the cancer tissue appears more important and, in most patients, intra-tumoural mutation heterogeneity may not significantly affect the efficacy of EGFR-targeted treatment [28]; however, further confirmation is needed.…”
Section: The Selection Of Biopsy Sitementioning
confidence: 99%
See 3 more Smart Citations